Hope on the inside eaudiobook - Bostwick, Marie (HighBridge Audio, 2019)
"Whatever comes your way, find the happiness in it." Hope Carpenter received that advice from her mother decades ago. Now, with their four children grown, Hope and her husband, Rick, are suddenly facing an uncertain future, after a forced retirement strains both their savings and their marriage. Seeking inspiration and a financial boost, Hope gets a job teaching crafts to inmates at a local women's prison. At first, Hope feels foolish and irrelevant, struggling to relate to women whose choices seem so different from her own. But with time, and the encouragement of the prison chaplain, she begins to discover common ground with the inmates, in their worries about their children and families, their fear of having failed those who need them. Just like her, they want to make something of themselves, but believe it might be impossible. Embarking on an ambitious quilting project, Hope and her students begin to bond. Together, piece by piece, they learn to defy expectations-their own and others'-and to see that it's never too late to stitch together a life that, even in its imperfections, is both surprising and beautiful.